Combined Administration of Curcumin and Chondroitin Sulfate Alleviates Cartilage Injury and Inflammation via NF-κB Pathway in Knee Osteoarthritis Rats - Guan, Ting; Ding, Liu-Gang; Lu, Bao-Yuan; Guo, Jia-Yi; Wu, Mei-Yin; Tan, Zhi-Qun; Hou, Shao-Zhen (Frontiers in Pharmacology, 2022)
Objective Osteoarthritis (OA) is a degenerative chronic disease that most often occurs in the knee joint. Studies have shown that some food supplements, such as curcumin and cartilage extract, are effective in treating knee OA (KOA) by exhibiting different protective effects. In this study, we further investigated the combined therapeutic effects of curcumin and cartilage extract on cartilage injury in rats with arthritis. Methods An experimental KOA model was induced by monosodium iodoacetate (MIA) in rats. All rats were randomly divided into 5 groups: Ctrl (healthy control); Model (KOA+ saline); Cur (KOA+ curcumin); CS (KOA+ cartilage extract); CA (KOA+ curcumin and cartilage extract) groups. The histomorphological changes of cartilage were observed by safranin-fixed green staining, H&E staining and micro-CT scanning. And the levels of PGE2, TNF-α and IL-1β in the arthral fluid and serum of each group were determined by the ELISA kit. The activities of SOD, CAT, COMP, MMP-3 and type II Collagen were detected by biochemical kits. The expression of TLR4, p-NF-κB, NF-κB and COX-2 in cartilage were detected by Western Blot. Results Data show that serum levels of IL-1β and MMP-3 were downregulated significantly in CA group with increased activity of SOD when compared to model group. Meanwhile, obvious repair of cartilage with higher contain of Collagen II could be observed in CA group than the ones in Cur or CS group. Besides, significant downregulation of the expression of p-p65 was found in CA group. Conclusion Our findings showed that combined administration of curcumin and cartilage extract could exert better repair for KOA in rat model.